Incidence, diagnosis, and treatment of enteric and colorectal fistulae in patients with Crohn's disease. - Michelassi, F (1993)
OBJECTIVE: The authors review their experience, evaluating the incidence and examining the various modalities employed in the diagnosis and treatment of patients with Crohn's disease complicated by fistulae. SUMMARY BACKGROUND DATA: Although common, internal and external fistulae in Crohn's disease may pose challenging problems to the surgeon. METHODS: Of 639 patients who underwent surgical treatment at the University of Chicago between 1970 and 1988 for complications of Crohn's disease, 222 patients (34.7%) were found to have 290 intra-abdominal fistulae. RESULTS: A fistula was diagnosed preoperatively in 154 patients (69.4%), intraoperatively in 60 (27%), and only after examination of the specimen in 8 (3.6%). The fistula represented the primary or single indication for surgical treatment in 14 patients (6.3%) and one of several indications in the remaining patients. Of 165 patients with an abdominal mass or abscess, 69 (41.8%) had a fistula. All patients underwent resection of the diseased intestinal segment; 160 (73.1%) with primary anastomosis and the remaining 62 with a temporary or permanent stoma. The fistula was directly responsible for a stoma in only 16 patients (7.2%) and was never responsible for a permanent stoma. Resection of the diseased bowel achieved en bloc removal of the fistula in 145 cases. Removal of 93 additional fistulae required resection of the diseased bowel segment along with closure of a fistulous opening on the stomach or duodenum (n = 14), bladder (n = 35), or rectosigmoid (n = 44). When the fistula drained through a vaginal cuff (n = 4), the opening was left to close by secondary intention; when the fistula opened through the abdominal wall (n = 46), the fistulous tract was debrided. In the remaining two entero-salpingeal fistulae, en bloc resection of the involved salpinx accomplished complete removal of the fistula. There was a dehiscence of one duodenal and one bladder repair; 14 patients (6%) experienced postoperative septic complications and one patient died. CONCLUSIONS: Fistulae are diagnosed preoperatively in 69% of cases and can be suspected in as many as 42% of patients with an abdominal mass. Fistulae are the primary or single indication for surgical treatment and are directly responsible for a stoma only in a few patients. Treatment, based on resection of the diseased bowel and extirpation of the fistula, can be accomplished with minimal morbidity and mortality.